An Empirical Analysis of Factors Inhibiting the Expansion of Mobile Number Portability in Nigeria - N , Odii Juliet; O.E , Osuagwu; V.E. , Ejiofor (African Journal of Education,Science and Technology (AJEST), 2022)
Mobile Number Portability (MNP) is not necessarily a new development in the mobile Telecommunications industry as it has been in existence since its initial implementation in Singapore in 1990. MNP enables subscribers to change their service providers without changing their telephone numbers. This novel technology was launched in Nigeria in 2013 by the Nigerian Communications Commission (NCC) and was expected to deepen competition among telecom service providers by improving the quality of service but has unfortunately failed to produce the desired impact. Two years after the implementation of MNP in Nigeria nothing has changed and as such subscribers are still reluctant to port their numbers due to envisaged restrictions. The objective of this research therefore is to identify these MNP restrictions, analyze them and ascertai Mobile Number Portability (MNP) is not necessarily a new development in the mobile Telecommunications industry as it has been in existence since its initial implementation in Singapore in 1990. MNP enables subscribers to change their service providers without changing their telephone numbers. This novel technology was launched in Nigeria in 2013 by the Nigerian Communications Commission (NCC) and was expected to deepen competition among telecom service providers by improving the quality of service but has unfortunately failed to produce the desired impact. Two years after the implementation of MNP in Nigeria nothing has changed and as such subscribers are still reluctant to port their numbers due to envisaged restrictions. The objective of this research therefore is to identify these MNP restrictions, analyze them and ascertain if they are actually responsible for the non adoption of MNP in Nigeria. The methodologies that we deployed in this research include hypothetic deductive methodology to extract the field data using questionnaire method and the statistical analysis methodology using multiple regressions and ANOVA of collected field data to extract the P-value . From the analysis, the f-cal α0.05 = 4.63609013 is greater than F-critical = 2.102384 and the P-value of 0.000108001 being less than = 0.05 indicates that the null hypothesis which says that “MNP has no relationship with the factors…” is rejected and we then accept the alternative which states that “MNP non adoption in Nigeria has relationship with factors…”. This has empirically shown that the identified factors are actually responsible for non workability of MNP in Nigeria. This research has shown that if government still allows the existing restrictions, subscribers may not be motivated to port.